Observation on The Use of Visual Scripting for Interaction Design Students - Yusup Sigit Martyastiadi (IJCAS (International Journal of Creative and Arts Studies), 2022)
Programming for Visual Communication Design students is a challenge in learning it. Their competencies are developing visual communication materials for interactive media designs. Programming competence in learning interaction design in the Visual Programming course focuses on programming logic. This study observes the method of visual programming using the Bolt add-on (visual scripting). This data was collected from students majoring in Interaction Design, Visual Communication Design Study Program at Universitas Multimedia Nusantara when they took Visual Programming courses. The indicators of this research are studying the understanding of programming logic from several materials and the learning outcomes of each observed material. The researcher found positive results using visual scripting in understanding programming logic for Visual Communication Design students on some of the material observed. In general, it can be concluded that the Bolt add-on in the UNITY game engine software can help students work on interactive media design projects. Observasi Penggunaan Pemrograman Visual untuk Mahasiswa Desain Interaksi Abstrak Pemrograman bagi mahasiswa Desain Komunikasi Visual menjadi tantangan tersendiri dalam mempelajarinya. Kompetensi mereka adalah mengembangkan materi komunikasi visual untuk desain media interaktif. Kompetensi pemrograman dalam pembelajaran desain interaksi pada mata kuliah Pemrograman Visual berfokus pada logika pemrograman. Penelitian ini mengamati penggunaan metode pemrograman visual dengan menggunakan aplikasi tambahan Bolt (visual scripting). Pengumpulan data ini dilakukan kepada mahasiswa peminatan Desain Interaksi, Program Studi Desain Komunikasi Visual, Universitas Multimedia Nusantara di saat mereka mengambil mata kuliah Pemrograman Visual. Indikator penelitian ini adalah mempelajari pemahaman logika pemrograman dari beberapa materi dan hasil belajar dari setiap materi yang diamati. Peneliti menemukan hasil positif menggunakan pemrograman visual dalam proses pemahaman logika pemrograman bagi mahasiswa Desain Komunikasi Visual pada beberapa materi yang diamati. Secara umum dapat disimpulkan bahwa aplikasi tambahan Bolt pada piranti lunak UNITY (game engine) dapat membantu mahasiswa dalam mengerjakan proyek perancangan media interaktif.